Enhancing Students’ Learning Outcomes and Motivation through Interactive Physics Escape in an LMS-Based E-Learning Environment - Liske Febi; Wasis Wasis; Muhammad Satriawan; Mita Anggaryani; Budi Jatmiko; Angeline Naomi Tan (Universitas Negeri Surabaya, 2026)
Objective: This study aims to (1) determine the level of feasibility, practicality, and effectiveness of the Interactive Physics Escape media; (2) evaluate the influence of media on students' learning motivation; and (3) analyze the influence of media use on improving learning outcomes on vibration, wave, and sound materials. Method: Using a Research and Development (R&D) approach combined with a quasi-experimental design (pretest-posttest control group), this study involved 60 junior high school students, namely the experimental and control groups. The experimental group implemented Interactive Physics Escape, an LMS-based escape room game that integrates ethnophysics (traditional Indonesian musical instruments), while the control group used direct instruction. Data was collected through tests and questionnaires, then analyzed descriptively and inferentially (Wilcoxon, Mann-Whitney, N-Gain, effect size). Results: Media was rated as very feasible (M=3.46–3.57), practical (M=3.64–3.86), and effective, especially in encouraging collaboration (M=3.93) and motivation (M=3.64–3.71). Statistical analysis showed a significant increase in learning outcomes in the experimental group (p<0.001) with a very strong effect size (r=-1.000). Furthermore, the post-test score and N-Gain of the experimental group (0.55, medium-high category) were significantly higher than those of the control group (p=0.003; N-Gain=0.38). Novelty: This research presents a new integration between escape room gamification, Learning Management System (LMS) technology, and an ethnophysical approach (using traditional Indonesian musical instruments as a learning context) in an integrated pedagogical intervention. The research results provide empirical evidence for a culture- and technology-based learning model that can simultaneously improve cognitive, affective and collaborative dimensions in science education.